KELAYAKAN PENGEMBANGAN USAHA INTEGRASI PADI DENGAN SAPI POTONG PADA KONDISI RISIKO DI KELOMPOK TANI DEWI SRI - Sumantri, Bayu; Fariyanti, Anna (Forum Agribisnis, 2011)
One of the alternative solutions for meet the target achieving a sustainable self-sufficiency in rice, the meat self-sufficiency, energy security, and in order to go organic agriculture is a way to integrate the development of rice with cattle. The purpose of this study is to analyze the feasibility of developing an integrated rice business with cattle in Farmers Group Dewi Sri and analyze the feasibility of developing an integrated rice business with cattle in the presence of production risk in rice output and prices in the Farmers Group Dewi Sri. Location of research conducted at the Farmers Group Dewi Sri, District Karawang, West Java. Techniques used in making the respondents using census techniques with reaponden number as many as 23 people. All non-financial and financial aspects the normal conditions and the incremental net benefits feasible to be made. Beside that, financial feasibility analysis of business development that integrates rice with cattle the risk of conditions of production and output prices of rice feasible to be made. Business development activities that integrate rice with cattle is very sensitive to changes in rice productivity and the highest level of risk on production risk.